Efektivitas Model Pembelajaran PjBL dengan Pendekatan Deep Learning untuk Meningkatkan Kemampuan Berpikir Reflektif Siswa Materi Metamorfosis Hewan - Tasya Putri Aprilia Wijayanti; Rosmiati Rosmiati; Erlin Ladyawati (Universitas Muhammadiyah Magelang, 2026)
This study aims to analyze the effectiveness of the Project-Based Learning (PjBL) model combined with a Deep Learning approach in improving students’ reflective thinking skills on the topic of animal metamorphosis in third-grade students at SDN Keboananom Gedangan. This research employed a quantitative approach using a quasi-experimental design involving two experimental classes. Data were collected through tests (pretest and posttest), observation sheets of teaching management, student response questionnaires, and reflective thinking attitude scales. Data analysis was conducted using the N-Gain test to measure the improvement in students’ reflective thinking skills. The results showed that the teacher’s instructional management was categorized as effective, with an average observation score of 42.5 in experimental class 1 and 39.5 in experimental class 2, indicating that the learning process was implemented well and consistently. Furthermore, students’ reflective thinking skills showed a significant improvement. In experimental class 1, the average pretest score of 41.6 increased to 92.20 in the posttest, with an N-Gain score of 0.87 (high category) and an improvement percentage of 86.43%. Meanwhile, in experimental class 2, the average pretest score of 43.96 increased to 87.08 in the posttest, with an N-Gain score of 0.77 (high category) and an improvement percentage of 76.66%. These findings indicate that the PjBL model combined with the Deep Learning approach is highly effective in enhancing students’ reflective thinking skills. This improvement occurs because students are actively involved in the learning process through project activities, discussions, exploration, and continuous reflection.